Performansi Sistem Pemanas Air Energi Surya Dengan Kolektor Parabolic Kapasitas Tangki 127 Liter - Willy Setiawan; Azridjal Aziz (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Nowadays, hot water is widely used as the daily needs for society and industry. As the bathing needs, society was used heating furnaces and electric furnaces for heating the water. Application of solar water heater collectors which used parabolic collectors is expected to be one solution in order to replace the them by utilizing abundant solar energy especially in Riau area. In this research the collector was made in form of half parabola by using a layer of shiny stainless plate in order to be able to reflect the heat energy which forward to the heat absorbent pipe that named copper pipe. The purpose of this research is to know the efficiency of collector and heat performance of collector as water heater. Dimension of solar water heater was used by parabolic collector with length of 170 cm, width of 88 cm and height of 30 cm and volume of tank which is about to 127 Liter. The tests of the data were tank water temperature, collector temperature, solar intensity, warm absorber pipe temperature and inlet and outlet temperatures. The results showed that the second day had better collector efficiency than the first day with an average efficiency of 54.89% and total efficiency of 933.18 KJ. The highest water temperature that the collector achieved in order to heat the water in the second day test was 50.2 ° C.Keywords: Parabolic collector, heat absorber pipe, solar water heater